Pengaruh Emotion Marketing Dan Experiential Marketing Terhadap Customer Loyalty Pondok Khas Melayu Di Pekanbaru - Osin Tauli; Marhadi ' (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2012)
This research is conducted to analyze the influence of emotion marketing and experiential marketing to customer loyalty Pondok Khas Melayu in Pekanbaru on Jl. Jend. Sudirman. The research consists of a dependent variable that customer loyalty (Y) and seven independent variables such as emotion marketing consists of product (X1) and equity (X2), while experiential marketing consists of sense (X3), feel (X4), think (X5 ), action (X6) and relate (X7). The population is the research a the customer’s of Pondok Khas Melayu with a sample of one hundred respondents by using purposive sampling. Data analysis using quantitatif methode with SPSS version seventeen. The result of this research convey that all of the independent variables simultaneously affect the cusromer loyalty significantly. At partially test only sense has affect significantly while the others independent variables affect not significantly. Adjusted R square show at moderate level (fifty six point two percent). It mean fourty three point eight percent has affect by other variable beyond this research. The conclution this research show only variable sense has affect to customer loyalty significantly. Therefore Pondok Khas Melayu restaurant should be pay attetion seriously to other independent variables this other to enhance the customer loyalty by delivered member card system, customer gathering, special discount / point value for member, etc.